1983
DOI: 10.1007/bf00998765
|View full text |Cite
|
Sign up to set email alerts
|

Attention and regulation of EEG alpha-attenuation responses

Abstract: Two experiments with 16 normal adults of both sexes tested the hypothesis that inattention to a biofeedback display is associated with increased variability of those physiological processes that had been regulated by the biofeedback. Each experiment was a repeated-measures-on-independent-subjects-design. Dependent variables were the time durations and the mean rms power of two mutually exclusive segments of the parietal-occipital EEG: alpha and not-alpha segments. Independent variables were combination of coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Neurofeedback therapy is mostly done over several sessions [3], though physiological effects of neurofeedback can already be observed after one session [13,31].…”
Section: Effects Of Alpha Neurofeedbackmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurofeedback therapy is mostly done over several sessions [3], though physiological effects of neurofeedback can already be observed after one session [13,31].…”
Section: Effects Of Alpha Neurofeedbackmentioning
confidence: 99%
“…Furthermore, an important difference of our study to therapeutic neurofeedback studies was that the feedback was not given as a discrete signal of success or failing to enhance alpha [31], but was visualised continuously. This might attenuate the saliency of the feedback and consequently of the reward.…”
Section: Effects Of Alpha Neurofeedbackmentioning
confidence: 99%
“…In the gaming scenario, however, the two tasks might impose a higher workload, as is a general issue in applications requiring the use of multimodal control [Fairclough, 2010]. Mulholland et al [1983] found indeed a decrease of the effect of neurofeedback when participants were also instructed to perform a counting task during the session, though the effect was still superior to a sham-feedback condition.…”
Section: Self-induction Of Relaxationmentioning
confidence: 92%
“…One of the relevant factors for the efficacy of neurofeedback seems to be the amount of training participants receive (Moore, 2005). Neurofeedback therapy is mostly done over several sessions [Ancoli and Kamiya, 1978;Hammond, 2007], though subjective or physiological effects of neurofeedback can already be observed after one session [Nowlis and Kamiya, 1970;Mulholland et al, 1983;Fell et al, 2002]. Consequently, a training protocol which incorporates multiple sessions and gives users the chance to train the brain activity that is used for the interface might yield effects.…”
Section: Self-induction Of Relaxationmentioning
confidence: 99%
See 1 more Smart Citation